Mechatronics '98 : proceedings of the 6th UK Mechatronics Forum International Conference, Skövde, Sweden, 9-11 September 1998 /: proceedings of the 6th UK Mechatronics Forum International Conference, Skövde, Sweden, 9-11 September 1998. (1998) - Unknown
No abstract available